Pelatihan Publik Speaking Untuk Meningkatkan Pelayanan Publik Pada Aparatur Pemerintah Desa Cahaya Negeri - Anita Marianata (CV. ITTC INDONESIA, 2025)
This community service activity begins by identifying problems in the community, especially the Cahaya Negeri village apparatus who have not been skilled in guiding events. Furthermore, in the implementation activities, good public speaking will be provided, in this activity, feedback activities will be given in the form of evaluation. The final step of the activity will be an evaluation and improvement of the results obtained during the activity. With good communication skills, village officials can convey information effectively, solve problems better, and provide more satisfactory services to the community.